Eastern Pennsylvania : includes Philadelphia, Gettysburg, Amish Country & the Pocono Mountains - Randall, Laura, 1967- (Woodstock, Vt. : Countryman Press, 2012)
A comprehensive guide to traveling in eastern Pennsylvania that provides information on transportation, sights, activities, outdoor areas, accommodations, restaurants, entertainment, shopping, and special events.
Philadelphia -- Southeastern Pennsylvania -- Bucks County -- Pennsylvania Dutch Country -- Lower Susquehanna River Valley -- Northeastern Pennsylvania.
Includes index.
Keywords: Pennsylvania -- Guidebooks; Pennsylvania; Guidebooks